Relationship between periodontitis-associated subgingival microbiota and clinical inflammation by 16S pyrosequencing - Camelo-Castillo, A; Novoa, L; Balsa-Castro, C; Blanco, J; Mira, A; Tomás, I (Journal of clinical periodontology, 2015)
Aim To analyse the relationship between the chronic periodontitis‐associated subgingival microbiota and clinical inflammation. Material and Methods Sixty subjects with generalized chronic periodontitis participated in this study. Patients were divided into two groups according to their bleeding on probing (BOP) scores: BOP‐1 group (mean scores ≤50% in sampled sites) and BOP‐2 group (mean scores >50%). Subgingival bacterial samples from periodontal patients were studied by pyrosequencing PCR products of the 16S rRNA gene and by real‐time PCR. Results In all the analysed subgingival samples, 102 bacterial genera and 203 species (from 41 genera of interest) were identified. Rarefaction curves showed a greater number of bacterial species in samples from BOP‐2 group compared to BOP‐1 group. The BOP‐1 group had significantly higher abundance percentages of Anaeroglobus (especifically, A. geminatus), Capnocytophaga (especifically C. gingivalis), TM7 and Veillonella. The BOP‐2 had significantly higher abundance percentages of Desulfobulbus (especially D. propionicus), Eubacterium (especially E. saphenum), Filifactor alocis, Streptococcus constellatus, Tannerella (especially, T. forsythia) and Treponema. Conclusion 16S pyrosequencing revealed that increased inflammation, at sites with periodontitis, is associated with a more diverse subgingival microbiota and specific changes in the bacterial composition, involving “established” periopathogens, symbionts and novel low‐abundance pathobionts.